Penyuluhan Deteksi Dini Ikterus Neonatorum Peran ASI dan Berat Badan Lahir dalam Pencegahan - Ayu irawati; Susianti Susianti; Arifa Usman; Sukmawati Sukmawati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Neonatal jaundice is a common health problem in newborns, characterized by yellow discoloration of the skin and sclera due to increased bilirubin levels in the blood. This condition, if not detected and treated properly, can lead to serious complications such as kernicterus, which can lead to long-term neurological developmental disorders. Risk factors contributing to jaundice include suboptimal breastfeeding practices, delayed initiation of breastfeeding, and low birth weight. Adequate breastfeeding from an early age plays a crucial role in accelerating the excretion of bilirubin through feces, while monitoring birth weight can help identify infants at risk of hyperbilirubinemia. This outreach activity aims to increase mothers' and families' knowledge about the importance of early and exclusive breastfeeding, as well as monitoring birth weight as a preventive measure for neonatal jaundice. The activity was conducted at Andi Makkasau Regional Hospital using lectures, interactive discussions, and the use of educational media such as leaflets and posters. The training materials covered the definition, risk factors, signs and symptoms of jaundice, early detection procedures, the benefits of breastfeeding in preventing jaundice, and the importance of recording and monitoring infant weight. The activity was evaluated through pre- and post-tests to gauge participants' understanding. The evaluation results showed a significant increase in participants' knowledge, particularly regarding the relationship between delayed breastfeeding, low birth weight, and an increased risk of neonatal jaundice. Furthermore, participants gained a better understanding of home-based measures to detect early symptoms and when to immediately take their baby to a health facility.